Strategi Komunikasi Internal Biro K3L Dalam Meningkatkan Budaya Keselamatan Kerja di PT PLN (Persero) UIP Sumbagut - Siregar, Almi Apriyansyah; Tanjung, Irwan Syari (Universitas Muhammadiyah Sumatera Utara, 2025)
Effective communication is a key factor in achieving organizational goals, especially in occupational safety and health programs. This study aims to analyze the internal communication strategy of the K3L Bureau in improving occupational safety culture at PT PLN (Persero) UIP Sumbagut. The research method used is descriptive qualitative, with the Lasswell communication model approach to understand the effectiveness of delivering occupational safety messages. Data collection techniques used in this study were observation, interviews, and documentation. Researchers conducted data analysis through three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study showed that the K3L Bureau utilized various communication media such as Instagram, WhatsApp, posters, banners, and email to disseminate occupational safety information to employees. The combination of various communication channels and active support from management proved to be important factors in increasing awareness and compliance with occupational safety culture.